Peran Mahasiswa dalam Mengatasi Penyebaran Covid-19 Melalui Sektor Pendidikan dan Ekonomi - Muhammad Torieq Abdillah; Anwar Hafidzi; Arie Sulistyoko (Fakultas Syariah UIN Antasari, 2020)
Abstract: The presence of the pandemic of Covid-19 in the world, especially in Indonesia create a new issue on all fronts of human life especially education sector and the economy. The problem faced is complicated enough that the government can't run itself for the sake of overcoming the spread of Covid-19. The presence of students surely make them are required in order to assist the government in addressing the problems of this new. The purpose of this study is to find out what is the role given by the student to assist the government in addressing the spread of Covid-19, especially in the education sector and the economy. This research uses the descriptive qualitative method. Data collection techniques in the form of a literature study. The results of this study show that the students have the idea that is very helpful and can be applied at this time so a little bit or the number able to help the government to confront Covid-19 so as not to spread widely. Abstrak: Hadirnya pandemi Covid-19 di dunia, terutama di Indonesia membuat masalah baru di semua lini kehidupan manusia terutama sektor pendidikan dan ekonomi. Masalah yang dihadapi cukup rumit sehingga pemerintah tidak bisa berjalan sendiri demi mengatasi penyebaran Covid-19. Adanya mahasiswa tentunya menjadikan mereka dituntut agar bisa membantu pemerintah dalam mengatasi permasalahan baru ini. Tujuan dari penelitian ini adalah untuk mengetahui apa peran yang diberikan oleh mahasiswa untuk membantu pemerintah dalam mengatasi penyebaran Covid-19 terutama dalam sektor pendidikan dan ekonomi. Penelitian ini menggunakan metode kualitatif deskriptif. Teknik pengumpulan data berupa studi kepustakaan. Hasil penelitian ini menunjukkan bahwa mahasiswa memiliki gagasan yang sangat membantu dan bisa diterapkan saat ini sehingga sedikit atau banyaknya mampu membantu pemerintah untuk menghadapi Covid-19 agar tidak menyebar secara luas.